Synthesis and Biological Evaluation of Substituted N-[3-(1H-Pyrrol-1-yl)methyl]-1,2,5,6-tetrahydropyridin-1-yl]benzamide/ benzene Sulfonamides as Anti-Inflammatory Agents - Gangapuram, Madhavi (2014)
The pharmacological activities of tetrahydropyridine (THP) derivatives are dependent on the substituent ring moiety. In this study, we investigate the anti-inflammatory activities of 12 newly synthesized substituted N-[3-(1H-pyrrol-1-yl)methyl]-1,2,5,6-tetrahydrobenzamide/benzene sulfonamides (9a–l) in murine BV-2 microglial cells. All compounds were initially screened for attenuation of nitric oxide (NO) production in lipopolysaccharide (LPS) (1 μg/mL)-activated microglial cells. The data show that only SO(2)-substituted THPs were effective at sub-lethal concentrations (IC(50) values of 12.92 μM (9i), 14.64 μM (9j), 19.63 μM (9k)) relative to L-N6-(1-iminoethyl)lysine positive control (IC(50) = 3.1 μM). The most potent SO(2)-substituted compound (9i) also blocked the LPS-inducible nitric oxide synthase (iNOS) and attenuated the release of several cytokines including IL-1α, IL-10, and IL-6. These findings establish the moderate immunomodulating effects of SO(2)-substituted THP derivatives.